1983
DOI: 10.1007/bf00315823
|View full text |Cite
|
Sign up to set email alerts
|

On the ultrastructure of the developing and adult mouse corneal stroma

Abstract: The EM study of the mouse embryonic cornea from the 12th to the 19th day of gestation as well as on postnatal days 2 and 18 and on adult animals allow the following conclusions to be drawn: 1. Immediately after the separation of the lens vesicle, the mesenchyme cells migrate into the cornea anlage. 2. There is no collagenous primary stroma in the mouse embryo. 3. During days 12-14 the stroma cells (fibroblasts) differentiate and develop the organelles required for ICS (intercellular substance) secretion. 4. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 16 publications
2
33
0
Order By: Relevance
“…The cells form long cytoplasmic processes and have a stellate, star-shaped phenotype. (2) As the number of cells between the lens and surface ectoderm continuously increases, the cells condense more and more to form several layers of flat mesenchymal cells that are separated from each other by a loose fibrillar extracellular matrix (Fig. 1B).…”
Section: Anterior Eye Development and The Role Of Ocular Mesenchymementioning
confidence: 99%
“…The cells form long cytoplasmic processes and have a stellate, star-shaped phenotype. (2) As the number of cells between the lens and surface ectoderm continuously increases, the cells condense more and more to form several layers of flat mesenchymal cells that are separated from each other by a loose fibrillar extracellular matrix (Fig. 1B).…”
Section: Anterior Eye Development and The Role Of Ocular Mesenchymementioning
confidence: 99%
“…The endothelium remains a monolayer throughout the entire development of the cornea and gradually thins with age. However, changes do occur during the time surrounding eyelid opening that likely have a profound effect on the endothelium becoming non-proliferative and initiating its barrier function (Bahn et al, 1986;Cintron et al, 1988;Haustein, 1983;Joyce et al, 2002;Murphy et al, 1984). Through electron microscopic studies, it has been demonstrated that, just before eyelid opening, intracellular spaces close and junctional complexes mature.…”
Section: Corneal Endotheliummentioning
confidence: 99%
“…The adult cornea is a lamellar tissue consisting of a stratified surface epithelial layer, a collagenous stroma sparsely populated by keratocytes and an inner endothelial layer. Embryonically, a region of surface ectoderm defined by the lens placode gives rise to the corneal epithelium as well as to the lens, whereas the corneal stroma and endothelium develop from cells originating in the neural crest (Haustein, 1983;Pei and Rhodin, 1970;Pei and Rhodin, 1971;Trainor and Tam, 1995). In the mouse, the corneal epithelium continues to mature after birth: at two weeks of age, the epithelium expands from two cell layers to a self-renewing, stratified epithelium comprising eight to ten cell layers (Hay, 1979;Zieske and Wasson, 1993).…”
Section: Introductionmentioning
confidence: 99%